Graphs and Their Applications in Various Fields (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article provides information on the theory of graphs, types of graphs and the application of graphs to various fields. A number of problems have been solved using graphs as examples. The article also contains a number of recommendations for math teachers on the use of graphs.